Um Modelo de Programação por Metas Estendido para o Planejamento de Radioterapia - Freitas, J.c. [UNESP] (2019)
In this paper an extended goal programming model applied to radiotherapy planning is proposed, in which the best weight combination was found to each goal. The model was applied to a real prostate cancer case and solved by the software CPLEX, where Logarithmic Barrier Interior Point Method was used.